A new approach to Indian federalism - Nayar, V.K. Sukumaran
In view of political developments abroad and in the India it is essential that we discard the outdated textbook approach to federalism that has held the ground in this country. A strong or weak centre connot be created by the provision of any constitution. All federal systems have to be operative in characters. We have a strong centre because the forces of integration are much stronger than the forces that clamour for seccession. The average Indian who want economic development and who hungers for the benefits of science and technology has a stake in a united India where decisions are arrived at by consensus. what is essential is that we discard the legalistic and bureaucratic approach to federation which
Keywords: Federal State - Relations; Centre - State Relations; Federalism; Federalism - India